An experimental study of wire breakage frequency on different electrodes during WEDM of Inconel-722. Issue 1 (October 2020) - Aggarwal, Vivek; Singh, Jujhar; Sharma, Shubham; Garg, Harish K.; Sharma, Abhinav; Singh, Gursharan; Parshad, Jwala
Abstract: Inconel 722 is a nickel-based superalloy that holds high strength and impervious to oxidation and corrosion at high temperatures. Wire electrical discharge machining (WEDM) was investigated as a superior alternative to conventional machining methods for intricate and complex shapes for materials containing more strength. However, these wire electrodes also undergo breakage during WEDM of Inconel 722 which unquestionably diminishes the efficiency of machining process, and accuracy. Therefore, this work is an effort to investigate and understand the phenomenon of wire breakage in relation to the combination set of Inconel 722 and three wire electrodes which are plain brass-wire, diffused brass-wire and zinc-covered metal wire. An experimental study was carried out to check the effect of six machining parameters viz. Ton, Toff, SV, IP, WF and WT on the frequency of wire breakage. Results demonstrate that zinc-covered metal wire has low breakage recurrence according to all the parameters of the process examined. It has also determined the optimal range of process-parameters under which zinc-coated brass-wire can be used to achieve effective machining.